Teaching suggestions for the measurement of area in Elementary School. Measurement tools and measurement strategies - KONSTANTINOS ZACHAROS; DIMITRIS CHASSAPIS (Metaichmio Publications, 2012)
The present study deals with teaching the concept and measurement of area. 106 subjects of the 6th grade of Greek Elementary School measured the area of different kinds of shapes. The subjects were divided into two groups, an experimental group and a control group. In the experimental group, area evaluation was taught in a way that highlighted the conceptual characteristics of area measurement. The teaching intervention and the use of different measurement tools led to different measurement strategies. Moreover, the experimental group used more successful strategies than the control group.